Mechanism of transition between separated and non-separated oil-water flows in inclined pipe - Dailu Zhang; Hongbing Zhang; Quan Ren; Xiang Zhao (Energy Exploration & Exploitation, 2023)
The analysis of drop formation and the transition between separated and non-separated oil–water flows enables us to better regulate flow parameters and pipe inclination angle, which is of great significance for improving the efficiency of oil transportation. Previous studies mainly carried out qualitative analysis through experiments and studied the transition between separated flows, very few studies are conducted on the transition between separated flow and dual continuous flow or intermittent flow. In addition, the influence of pipe inclination angle was not considered in the study of drop formation, which results in inadequate force analysis of drop. This article presents the use of dimensionless numbers to predict the transition between separated flow and dual continuous flow or intermittent flow. The relation expression between dimensionless numbers is obtained by regression of experimental data. The critical values of flow parameters and pipe inclination angle can be calculated by the relation expression between dimensionless numbers and flow parameters. In addition, this article proposes a three-dimensional interfacial wave shear deformation mechanism by adding volume forces to the force analysis for the possible inclined pipe. The prediction equation is obtained and the critical value of flow parameters and pipe inclination angle for drop formation can be calculated, which are in good agreement with the experimental data.